Uji Efektivitas Salep Ekstrak Etanol Daun Buni (Antidesma bunius (L.) Spreng) Sebagai Penyembuhan Luka Bakar Grade II (A) Pada Mencit - I Made Agus Sunadi Putra; Ni Komang Ayu Trias Pradnyawati; I Gusti Agung Ayu Kusuma Wardani (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Grade II (A) burn wounds are a common form of skin injury that require proper management to accelerate the healing process and prevent complications. The use of natural products as alternative topical therapies continues to be developed because they are considered safer and possess diverse biological activities. Buni leaves (Antidesma bunius (L.) Spreng) are known to contain bioactive compounds such as flavonoids, tannins, saponins, and alkaloids that potentially support skin tissue regeneration. This study aimed to grade II (A) burn wounds in male white mice (Mus musculus). This study employed an experimental method with a post-test only control group design. The animals were divided into five groups: negative control, positive control (Bioplacenton®), and treatment groups receiving buni leaf extract ointment at concentrations of 2.5%, 5%, and 10%. Grade II (A) burns were induced on the dorsal area of the mice, followed by treatment according to each group. Observations were conducted for 14 days by measuring wound diameter reduction and percentage of wound healing. The data were analyzed statistically using One Way ANOVA followed by a post hoc test to determine differences between treatment groups. The results showed that all concentrations of buni leaf extract ointment accelerated burn wound healing compared to the negative control, with the 10% concentration demonstrating the highest effectiveness and a statistically significant difference (p<0.05). It can be concluded that the 96% ethanolic extract ointment of buni leaves has the potential to be developed as a natural topical preparation for grade II (A) burn therapy. determine the effectiveness of a 96% ethanolic extract ointment of buni leaves in accelerating the healing of